Physical inactivity induces insulin resistance in plantaris muscle through protein tyrosine phosphatase 1B activation in mice - Kakehi, Saori; Tamura, Yoshifumi; Ikeda, Shin-ichi; Kaga, Naoko; Taka, Hikari; Nishida, Yuya; Kawamori, Ryuzo; Watada, Hirotaka (Frontiers in Physiology, 2023)
Inactivity causes insulin resistance in skeletal muscle and exacerbates various lifestyle-related diseases. We previously found that 24-h hindlimb cast immobilization (HCI) of the predominantly slow-twitch soleus muscle increased intramyocellular diacylglycerol (IMDG) and insulin resistance by activation of lipin1, and HCI after a high-fat diet (HFD) further aggravated insulin resistance. Here, we investigated the effects of HCI on the fast-twitch–predominant plantaris muscle. HCI reduced the insulin sensitivity of plantaris muscle by approximately 30%, and HCI following HFD dramatically reduced insulin sensitivity by approximately 70% without significant changes in the amount of IMDG. Insulin-stimulated phosphorylation levels of insulin receptor (IR), IR substrate-1, and Akt were reduced in parallel with the decrease in insulin sensitivity. Furthermore, tyrosine phosphatase 1B (PTP1B), a protein known to inhibit insulin action by dephosphorylating IR, was activated, and PTP1B inhibition canceled HCI-induced insulin resistance. In conclusion, HCI causes insulin resistance in the fast-twitch–predominant plantaris muscle as well as in the slow-twitch–predominant soleus muscle, and HFD potentiates these effects in both muscle types. However, the mechanism differed between soleus and plantaris muscles, since insulin resistance was mediated by the PTP1B inhibition at IR in plantaris muscle.